Rethinking financial distress in public healthcare: evidence from Greek hospitals’ governance attributes - Karakolias, Stefanos (Frontiers in Public Health, 2025)
BackgroundFinancial distress remains a relatively underexplored area in public healthcare, although such failures occur globally, demonstrating that maintaining public health requires strategies to ensure financial stability and the continuous operation of public healthcare organizations. This study aims to assess financial distress and its relationship with hospital-specific governance attributes by examining the case of Greek public hospitals.MethodsTo achieve this aim, Altman’s Z”-score model was applied to the entire range of public hospitals. The attributes investigated included hospital size, location, specialty, and manager gender. All data were retrieved from published financial statements for 2022. The analysis employed descriptive statistics, normality tests, correlations, and non-parametric tests.ResultsThe findings indicate strong financial viability, reflected in high Z-scores driven by low financial leverage and ample working capital. In addition, both smaller units and women-led hospitals outperformed others in terms of Z-scores. However, heavy reliance on state subsidies, the slow collection of non-current hospital bills, and the rising levels of indebtedness suggest a financial condition substantially weaker than that implied by Z-scores or any other model based solely on financial statement data.ConclusionFinancial distress requires redefinition in the context of public entities, since their closure is not a core strategy. Existing definitions and prediction models fail to account for the support mechanisms that mask poor financial viability, effectively shifting financial distress to key stakeholders such as suppliers and the state owner.